Differences in the Effect of Deep Breathing and Prone Position on the Oxygen Saturation Value among COVID-19 Survivors in a Sub-district of East Java Province - Sunarto Sunarto; Lilis Devy Anggraini; Addi Mardi Harnanto (Journal of Bionursing, 2023)
Background. To date, the COVID-19 pandemic has become a major problem in all countries of the world. Indonesia registered as a country with a significant drop in cases. The highest percentage of outcomes in COVID-19 survivors were fatigue and shortness of breath. Medical rehabilitation therapy for COVID-19 survivors is critically needed to maintain and improve quality of life by preventing or reducing the development of functional impairment and disability and by ameliorating and reducing complications. Methods. Quasi-experimental research design with pretest-posttest design on COVID-19 survivors. The sample is 120 respondents consisting of 60 respondents in the Deep Breathing group and 60 respondents in the Prone position group. Results. The study showed that there was a significant difference in oxygen saturation value (ρ value 0.004 < 0.05) between the Deep Breathing and the Prone in COVID-19 survivors. Conclusion. There is a significant difference (ρ 0.004) in oxygen saturation values in COVID-19 survivors who are given Deep Breathing and Prone position.